Mechanism by which untwisting of retinal leads to productive bacteriorhodopsin photocycle states - Wolter, Tino; Elstner, Marcus; Fischer, Stefan; Smith, Jeremy C.; Bondar, Ana-Nicoleta (The journal of physical chemistry. B, Biophysics, biomaterials, liquids, and soft matter, 2015)
Relaxation of the twisted-retinal photoproduct state triggers proton-coupled reaction cycle in retinal proteins. Given the crowded protein environments in which the retinal resides, a key open question is whether the retinal relaxation path is governed by the intrinsic torsional properties of the retinal or rather by the interactions of the retinal with protein and water groups. Here we address this question by performing systematic quantum mechanical/molecular mechanical molecular dynamics computations of retinal dynamics in bacteriorhodopsin at different temperatures, reaction path computations, and assessment of the vibrational fingerprints of the retinal molecule. The results demonstrate a complex dependence of the retinal dynamics and preferred geometry on temperature. As the temperature increases, the retinal dihedral angle samples values largely determined by its internal conformational energy. The protein environment shapes the energetics of retinal relaxation and provides hydrogen-bonding partners that stabilize the retinal geometry.